2021
DOI: 10.17221/316/2021-pse
|View full text |Cite
|
Sign up to set email alerts
|

Oil content and fatty acid profile of selected poppy (Papaver somniferum L.) landraces and modern cultivars

Abstract: The oil content and fatty acid composition were determined in the seed of 19 poppy genotypes (both landraces and modern cultivars) grown in three-year field trials. The total oil content ranged from 34.56–44.76%. The oil content in white-seeded genotypes (40.73–44.76%) exceeded the oil content in blue-seeded genotypes (34.56–40.34%) and ocher-seeded genotypes (38.36–42.69%). Linoleic acid (71.41–74.02%), oleic acid (12.35–15.51%) and palmitic acid (8.95–10.29%) were the most abundant fatty acids in the evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…However, to the best of our knowledge, there are no data for the fatty-acid profile of corn poppy pollen, although there are extensive data on the lipid composition of poppy seeds and some other corn poppy plant parts. Based on the obtained results, it can observed that the lipid fraction of PBP is in line with the available data for poppy seeds, showing significant predominance of unsaturated FAs [56][57][58][59]. Nevertheless, the distribution of single acids differs in bee-collected pollen compared with poppy-seed composition.…”
Section: Gc-fid Fatty-acid Profile Of Pbpsupporting
confidence: 85%
See 1 more Smart Citation
“…However, to the best of our knowledge, there are no data for the fatty-acid profile of corn poppy pollen, although there are extensive data on the lipid composition of poppy seeds and some other corn poppy plant parts. Based on the obtained results, it can observed that the lipid fraction of PBP is in line with the available data for poppy seeds, showing significant predominance of unsaturated FAs [56][57][58][59]. Nevertheless, the distribution of single acids differs in bee-collected pollen compared with poppy-seed composition.…”
Section: Gc-fid Fatty-acid Profile Of Pbpsupporting
confidence: 85%
“…Nevertheless, the distribution of single acids differs in bee-collected pollen compared with poppy-seed composition. For instance, linoleic acid was predominantly found in seed samples [56][57][58], whereas in the case of PBP, docosahexaenoic acid (DHA) followed by α-linolenic acid were the main FAs. It has also been documented that α-linolenic acid is one of the predominant FAs in the leaves of corn poppy plants [60].…”
Section: Gc-fid Fatty-acid Profile Of Pbpmentioning
confidence: 99%
“…Tung oil 160 1-1.2 [24] Linseed oil 170 1.2-2.5 [17,25] Sesame oil 100 1.5-2 [18] Rapeseed oil 94 2-3 [26] Walnut oil 132 2-3 [27,28] Poppy oil 140 3-5 [29] Perilla oil 190 2-4 [30,31] 2.3.2. Procedures for Quantitative GC-MS Analysis of Amino Acids as Tert-Butyldimethylsilyl (TBDMS) Derivatives Saponification and methylation were performed in a 0.2 M solution of m-(trifluoromethyl) phenyltrimethyl ammonium hydroxide (m-TFPTAH) in a 2:1 (v/v) mixture of methanol and toluene (20 µL) [32,33].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, poppy, melon, and pumpkin seed oils contain a major proportion of linoleic acid (ω-6). In the case of poppy seed oil, the content of linoleic acid exceeds 70% [ 17 ], while in melon or pumpkin seed oils, this content usually represents between 40 and 60% [ 18 , 19 ]. The high content of unsaturated fatty acids in these oils gives them a liquid consistency at room temperature.…”
Section: Introductionmentioning
confidence: 99%